2012
DOI: 10.1258/acb.2012.011215
|View full text |Cite
|
Sign up to set email alerts
|

Activated platelet-derived microparticle numbers are elevated in patients with severe fungal (Candida albicans) sepsis

Abstract: The measurement of CD42a- and PAC1-positive microparticles may provide important additional information which can help to improve the early instalment of antifungal therapy of severe septic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 28 publications
2
30
1
1
Order By: Relevance
“…However, PDMP assays may consist of quantifying assays, functional assays and morphologic assays. Although the ISTH report was a first step towards achieving standardization of assay methods for evaluating PDMPs, studies continue to use different assay types [24][25][26][27][28][29][30][31][32] . Strasser and coworkers showed a good correlation among three different methods of characterizing PDMPs and suggested that an analysis method other than FCM should be used concurrently to detect MPs when the PDMP size is below the limit of detection on FCM 24) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PDMP assays may consist of quantifying assays, functional assays and morphologic assays. Although the ISTH report was a first step towards achieving standardization of assay methods for evaluating PDMPs, studies continue to use different assay types [24][25][26][27][28][29][30][31][32] . Strasser and coworkers showed a good correlation among three different methods of characterizing PDMPs and suggested that an analysis method other than FCM should be used concurrently to detect MPs when the PDMP size is below the limit of detection on FCM 24) .…”
Section: Discussionmentioning
confidence: 99%
“…Woth and coworkers showed that different surface antigens of PDMPs are elevated in subjects with or without fungal infection (CD42a) 28) . Therefore, the measurement method recommended by the ISTH, which uses only a single antigen (CD41), might be too limited for assessing PDMPs.…”
Section: Max Pdmp/plts Ratio For Predicting Hospital Mortalitymentioning
confidence: 99%
“…For Candida albicans , it is known that this species interacts with platelets in vitro [19, 20], and high numbers of microparticles shed from activated platelets are detected in patients with severe Candida sepsis [21]. Candida albicans strains that are susceptible in vitro to platelet-derived microbicidal peptides (PMP) show decreased virulence in a rabbit model [22].…”
Section: Introductionmentioning
confidence: 99%
“…In neutropenic patients the base line platelet count is one predictive parameter for invasive aspergillosis [156] and thrombo cytopenia in liver transplant recipients increases the risk for fungal infections [157]. Elevated numbers of plateletderived microparticles, as found during severe sepsis caused by C. albicans [158], further underline the relevance of these blood cells in fighting fungal infections. Recent insights in the host-pathogen interplay during fungal infec tions have revealed diverse relations between platelets and infectious fungal propagules.…”
Section: Platelets In Fungal Infectionsmentioning
confidence: 99%